Implementing time-driven activity-based costing for unused capacity measurement in local university - Sri Nur Areena, Mohd Zaini; Mohd Yazid, Abu (MDPI, 2023)
All university departments must maximize their use of time and resources in order to meet their goal with the least amount of waste. The existing system in a local university does not implement the time equation and so the processing time determined is not in accordance with the actual processing time of every activity. Thus, the present implementation in the organization does not illustrate the correlation between the supplied resources and the practical capacity. The purpose of this study was to build a new costing structure using time-driven activity-based costing for academic staff. This work considered annual Key Performance Indicator Analysis data for the year 2020 with 53 sub parameters; this was from an engineering faculty for lecturers in two different grades with 12 and 27 samples, respectively. Eventually, there were 3 and 16 samples in grade DS45 and DS51/52, respectively, that have an insufficient time capacity. The remaining samples in both grades then had an unused time capacity, which ultimately resulted in unused cost capacity, also known as waste cost. This work was able to discover the total amount of used time that results in used, unused, or otherwise insufficient capacity, after analyzing the capacity cost using Time-Driven Activity- Based Costing.